MARXISM & PSYCHOLOGY CONFERENCE – 2010 - Parker, Ian (PINS-Psychology in Society, 2025)
The Marxism & Psychology conference took place from 5-7 August at the University of Prince Edward Island, Canada. Around 100 participants from around the world discussed the intersection between different traditions in psychology and different strands of Marxism. The Island is the site of a number of political-economic cultural forces, ranging from the minority “Acadian” community descended from French settlers (the Acadians were expelled from the Island by the British and some ended up in Louisiana where they become known as “Cajuns”) to the Mi’q Maks who are now mainly confined to the much tinier Lennox Island off the coast of the main island (where they sell tacky souvenirs, including parmesan flavour dog biscuits in the shape of Prince Edward Island). These potent reminders of the history of colonialism and class were sidestepped in the conference by a focus instead on Anne of Green Gables (the musical is in its 46th year and “all things Anne” sustain the tourist trade). I put together the main sessions, so this is also a self-critique.